Mengungkap Pengaruh Biaya Perdagangan dan Faktor Risiko terhadap Kinerja Hedge Fund - Ngadi Permana; Mohammad Chaidir; Sri Utami Nurhasanah (Master Manajemen, 2024)
This study examines the impact of trading costs and related factors on the unobserved performance of hedge funds through a qualitative literature review approach. The review covers recent studies on explicit and implicit costs, liquidity risk, portfolio complexity, hedge fund size, and risk management strategies. The findings reveal that trading costs significantly affect the net returns of hedge funds, while liquidity risk and portfolio complexity hinder asset management efficiency. Large hedge funds benefit from economies of scale but face challenges in risk management and transparency. The study also highlights that data-driven risk management strategies can enhance long-term return stability. This research underscores the need for a holistic evaluation to understand hedge fund performance and discusses limitations associated with the qualitative approach.